Oncolytic measles virus strains as novel anticancer agents - Pavlos Msaouel; Mateusz Opyrchal; Evidio Domingo‐Musibay; Evanthia Galanis (2013)
Introduction: Replication-competent oncolytic measles virus (MV) strains preferentially infect and destroy a wide variety of cancer tissues. Clinical translation of engineered attenuated MV vaccine derivatives is demonstrating the therapeutic potential and negligible pathogenicity of these strains in humans. Areas covered: The present review summarizes the mechanisms of MV tumor selectivity and cytopathic activity as well as the current data on the oncolytic efficacy and preclinical testing of MV strains. Investigational strategies to reprogram MV selectivity, escape antiviral immunity and modulate the immune system to enhance viral delivery and tumor oncolysis are also discussed. Expert opinion: Clinical viral kinetic data derived from noninvasive monitoring of reporter transgene expression will guide future protocols to enhance oncolytic MV efficacy. Anti-measles immunity is a major challenge of measles-based therapeutics and various strategies are being investigated to modulate immunity. These include the combination of MV therapy with immunosuppressive drugs, such as cyclophosphamide, the use of cell carriers and the introduction of immunomodulatory transgenes and wild-type virulence genes. Available MV retargeting technologies can address safety considerations that may arise as more potent oncolytic MV vectors are being developed.